Centipede Scolopendra suppresses cell growth in human epidermoid carcinoma cell A431 - Zheng, Lei; He, Hao; Shen, Xuji; Sun, Yanping (Bangladesh Journal of Pharmacology, 2017)
The aim of this study was to examine the anti-proliferation and anti-migration effect of Centipede Scolopendra extracts (CSE) on human epidermoid carcinoma cells (high-EGFR expression) A431 and elucidate the underlying signaling mechanisms. MTT and colony formation assays were used. Migration and invasion potential of A431 cells were examined by wound-healing assays and matrigel invasion chamber assays. To investigate the underlying molecular mechanisms, we used ELISA to analyze the expression of EGF, Western blotting to analyze the expression of MMP2 (matrix metalloproteinase 2), MMP9 and EGFR, PCR to analyze the mRNA expression of EGFR pretreated with CSE. The results showed that CSE effectively inhibited the proliferation of A431. Furthermore, CSE-mediated cell cycle arrest in S phase. We also observed that CSE treatment led to down-regulation of MMP2 and MMP9 and suppress the migration and invasion in A431. CSE exerted its anti-proliferation and anti-migration by targeting EGFR and related metastasis factors, thus could be a useful therapeutic candidate for high-EGFR expression cancer intervention. Video Clip of Methodology: Cell migration and invasion assay: 2 min 41 sec Full Screen Alternate